Utilization of Sudanese sidr (Ziziphus spina-christi L) for jam manufacture - Altayp, Altayp Abd arahman; Abdel-Rahman, Nawal Abdel-Gayoum (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The purpose of this study was to assess the physicochemical properties of sidr (Zizyphus spina-christiL) fruits (Nabaq). As well as, to choice the best extraction method, processing Nabaq jam and evaluate its suitability during storage. The jam processed from Nabaq pulp was filled into glass jars containers. Organoleptic attributes, physico-chemical properties were carried out for the processed jams. Total soluble solids (TSS), pH, total titratable acidity (TTA), total and reducing sugars were determined. The results showed that the Nabaq forest fruit contains high level of energy, vitamin C, betacarotene and protein. As well as, contain several minerals such as Na, K, Ca, Mg and P. The results observed that the highest yield of cold and hot extraction; from 20 kg Nabaq; were 19.09 and 13.75 g with total soluble solids of 3 and 2%, respectively. The developed Nabaq jam had 68 %, 3.40, 0.30, 40.95 and 7.39 as levels of TSS %, pH, TTA %, total reducing sugars. The developed jams (without and with pineapple flavuor) were showed that no significant (P>0.05) differences in quality attributes, and the panelist were accepted both of jams.